Pengaruh gaya kepemimpinan kepala sekolah yang tidak berkompeten terhadap nasib siswa SMAN 1 Mempawah - Syahariya, Aura Anya; Al Azhari, Muh. Ubaidillah (Maliki Interdisciplinary Journal, 2025)
The National Achievement-Based Selection (SNBP) has become the primary pathway for high-achieving students across Indonesia to pursue higher education at state universities. Unfortunately, a significant number of students have had to abandon their dreams because schools fail to complete the finalization process of the School and Student Data Base (PDSS). This research aims to analyze the influence of incompetent school principal leadership models on the fate of students at SMAN 1 Mempawah and to evaluate the impact of school administrative negligence on students' opportunities to achieve their desired State Universities. The approach used in this research is a qualitative method with case studies. Data collection was carried out through reading materials and analysis of documents related to the issues at hand. The results of the study indicate that various forms of school negligence, especially incompetent school principal leadership models, such as errors in data entry, delays in submitting files, and lack of academic guidance and information regarding selection, are the main factors that hinder students. This research concludes that the competence of the school principal plays a very important role in determining student success.